P-088 HOW TO REPAIR A LATERAL INCISIONAL ABDOMINAL WALL HERNIA?. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Palibrk, I; Velickovic, J; Djukanovic, M; Bogdanovic, M; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To present our original method for surgical treatment of patients with lateral incisional hernia (LIH) Material and Method: Patients with LIH and simultaneous presence of a middle incisional hernia (MIH) were treated by our original technique based on the principles of anterior component separation technique and sublay technique: a) skin and subcutaneous tissue incision along the midline and MIH dissection; b) subcutaneous tissue dissection in the lateral direction to the Spiegel line or the LIH lateral edge on the side of the LIH; c) vertical incision of the external oblique muscle (EOM) lateral to the Spiegel line or the LIH; d) the rectus muscle (RM) dissection from its posterior sheath on the opposite side of the LIH; e) suturing the posterior rectus sheath on the opposite side of the LIH with RM on the side of the LIH; f) suturing of the internal oblique muscle with the lateral edge of the RM on the side of the LIH; g) onlay polypropylene mesh hernioplasty. Results: Between January 2013 and May 2022, 44 consecutive patients with LIH+MIH underwent surgery. A median (range) LIH defect surface was 90 (20–270) cm2. During mean follow up of 14 months postoperative complications occured in seven (15, 9%) patients: seroma in three, hematoma in two, mesh infection and hernia recurrence in one. Conclusion: Our original method can be one of the good solutions for simultaneous treatment of LIH and MIH.